Association Between Opioid-Related Mortality and History of Surgical Procedure: A Population-Based Case-Control Study - Mhd Wasem Alsabbagh, BScPhm, PhD; Michael A. Beazely, BSP, PhD; Leona Spasik, PharmD (Annals of Surgery Open)
Objective:. This study examined whether there is an association between opioid-related mortality and surgical procedures. Methods:. A case-control study design using deceased controls compared individuals with and without opioid death and their exposure to common surgeries in the preceding 4 years. This population-based study used linked death and hospitalization databases in Canada (excluding Quebec) from January 01, 2008 to December 31, 2017. Cases of opioid death were identified and matched to 5 controls who died of other causes by age (±4 years), sex, province of death, and date of death (±1 year). Patients with HIV infection and alcohol-related deaths were excluded from the control group. Logistic regression was used to determine if there was an association between having surgery and death from an opioid-related cause by estimating the crude and adjusted odds ratios (ORs) with the corresponding 95% confidence interval (CI). Covariates included sociodemographic characteristics, comorbidities, and the number of days of hospitalization in the previous 4 years. Results:. We identified 11,865 cases and matched them with 59,345 controls. About 11.2% of cases and 12.5% of controls had surgery in the 4 years before their death, corresponding to a crude OR of 0.89 (95% CI: 0.83–0.94). After adjustment, opioid mortality was associated with surgical procedure with OR of 1.26 (95% CI: 1.17–1.36). Conclusions:. After adjusting for comorbidities, patients with opioid mortality were more likely to undergo surgical intervention within 4 years before their death. Clinicians should enhance screening for opioid use and risk factors when considering postoperative opioid prescribing.